Salmonellatyphi and endocarditis: a systematic review of case reports - Jabeen, Kokab; Bint Ali, Sameen; Tufail, Zainab; Mustafa, Sana; Chaudhry, Mahnoor; Tahir, Muhammad J.; Asghar, Muhammad Sohaib; Ahmed, Ali (Frontiers in Medicine, 2024)
Salmonella Typhi, is gram-negative bacterium responsible for typhoid fever, can infect the inner lining or valves of the heart and cause endocarditis. This systematic review aims to report cases of Salmonella Typhi-associated endocarditis and its clinical features.This systematic review was reported as per the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) checklist. Only case reports and case series reporting endocarditis caused by Salmonella Typhi, irrespective of age, gender, and demographics, were deemed eligible for inclusion. To identify relevant studies, a literature search was conducted using relevant keywords over PubMed, Google Scholar, and Cochrane Library from inception till 31st December 2023. Following study selection, relevant data was extracted into table 1 and pooled in terms of frequencies and percentages. A quality assessment was performed using the Joanna Briggs Institute Critical Appraisal Checklist for Case Reports.This review included seven case reports comprising 22.2% female and 77.8% males. The mean age of patients was 27.9+12.0 years. Regarding past medical history, 33.3% (3/9) of patients had a previous cardiac pathology. Fever remained the most common complaint (88.9%). Transthoracic and transesophageal echocardiography remained the mainstay of diagnosis in all cases, with identified vegetations involving the mitral, aortic and tricuspid valve in 33.3%. Ceftriaxone with or without gentamycin remained the choice of antibiotic for 88.9% cases, and all patients responded to the offered treatment.Salmonella Typhi-associated endocarditis, though rare, presents unique challenges and requires timely diagnosis. This systematic review of seven cases highlights a predominantly male population affected, with a mean age in the third decade, suggesting a higher invasiveness compared to other causes. The findings from this study underscore the importance of early recognition and appropriate management, primarily with antibiotic therapy. Further research with larger cohorts is crucial to refine understanding and guide policymaking for this rare but life-threatening condition.